Translocating under the radar: an investigation into the secretion pathway of EspC, a ‘classical’ autotransporter from enteropathogenic E. coli - Serdar, Marina (2023)
Autotransporter proteins (ATs) are a family of diverse, surface-accessible virulence factors produced by numerous Gram-negative bacteria and utilise the Type V Secretion System (T5SS). Conserved domains direct AT secretion, and it has recently been revealed that chaperones assist ATs across the cell membrane, disputing the ‘auto’ in their name. Elucidating the steps of AT secretion will help the development of new antivirulence therapies. This study follows previous findings that the cytotoxic EPEC AT EspC localises into helical patches along the bacterial cell during secretion. The helical pattern resembles those of the actin homologue MreB and the Sec translocon. Disruption of either resulted in an altered EspC localisation. Here, an extended range of Sec temperature-sensitive (ts) mutants was used to probe EspC localisation at different steps of IM translocation. SecAts and SecYts mutants exhibited bipolar localisation of EspC, whilst SecDts and SecFts yielded no detectable EspC, supporting the role of the Sec translocon in EspC targeting. Next, the colocalisation of EspC-mCherry and MreB-TC in E. coli MG1655 was detected using super-resolution Structured Illumination Microscopy. The two proteins remained associated following treatment with a MreB polymerisation inhibitor, A22. To map EspC interactions on its way out of the cell, steps were taken to photo-crosslink EspC with the pBpa unnatural amino acid to substantiate the microscopy findings and discover more protein partners. An extracellularly labelled EspC has also been constructed using SpyCatcher technology for studying EspC during EPEC infections of intestinal epithelial cells with the intention of illuminating its internalisation into host cells. By discerning the protein-protein interactions and elucidating the secretion pathway of EspC, the ultimate aim is to gain insight into ATs of related enteric pathogens to underpin the development of new antimicrobials. Finally, EspC secretion was tracked during treatment with a promising T3SS antivirulent (Aurodox). It was confirmed that its potency extends to EspC (T5SS) because it shares T3SS’s transcriptional regulator (Ler).